New modeling formalism for the energy simulation of conveyor systems - Ham, Won K.; Oh, J. W.; Cho, Kang H.; Park, Kiejin; Park, Sang C. (Computers and Industrial Engineering, 2019)
Presented in this paper is a modeling formalism for the energy simulation of conveyor systems. Reducing the energy consumption of a conveyor system can decrease a significant portion of the operation cost, contribute to the sustainable operation, and prepare for future energy cost increases related to regulations for green industry. Therefore, the energy consumption is becoming one of the key performance indicators in conveyor systems design. To construct a simulation model considering the energy consumption of conveyor systems, the modeling formalism is necessary to represent the multiple material transportations and conveyor operation switching (on and off) depending on material load states. This paper proposes a new modeling formalism satisfying the requirements by extending the conventional discrete event system specification (DEVS) formalism. In the proposed formalism, each simulation entity has an energy model, which is derived from the reverse engineering of real conveyor operations, to determine energy consumption states and rates. The simulation results of this research have been applied to the revision of a warehouse conveyor system in Korea.
Keywords: Conveyor systems; Discrete event system specification; Energy simulation; Key performance indicators; Modeling formalisms; Multiple materials; Simulation model; Sustainable operations; Conveyor system; Discrete-event system; Energy simulation; Modeling formalism